(untitled) (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2021)
This paper offerings a software architecture that supports Google Assistant integration which is useful for search engine and further it will be used for in TV application, designed for Android operating system. In order to understand the capability of voice assistant (VA), The task of this research was to assess its responses to PPD questions in terms of accuracy, verbal response. Most systems on the market use a Raspberry Pi or Arduino chipset that is programmed to control a number of devices in a home that are instructed through a mobile app or web-based user interface. Nowadays, Google Assistant is becoming more and more widespread personal assistant and people commonly use it’s features in the applications on their, smart’ devices such as smartphones, smart digital television receivers, smartwatches, etc. The majority of existing speech recognition tools provides the result of the speech processing in a free form textual output or structured form textual output.